Buliding N1™ Grid Solutions Preparing, Architecting, and Implementing Service-Centric Data Centers - Carolan, Jason; Radeztsky, Scott; Strong, Paul; Turner, Ed (Sun blueprints, 2004)
The N1 Grid is Sun's vision, strategy, and architecture-and a set of products-that redefine the nature of data center computing. The N1 Grid architecture uses the network, physically and logically, as its fundamental organizing principle. This book enables the reader to implement service-centric data center solutions through the use of N1 Grid-based principles and architectures, which are more efficient and flexible. It opens with an overview of how this approach evolved and then takes the reader through the process of preparing, architecting, and implementing N1 Grid-based solutions.